Quality of forest biomass pellets produced in State of Santa Catarina for power generation Qualidade dos pellets de biomassa florestal produzidos em santa catarina para a geração de energia - Spanhol A.* (2015)
Quality of forest biomass pellets produced in State of Santa Catarina for power generation. This study aimed to determine the physical, chemical and energetic properties of pellets of residual forest biomass of Pinus spp. production chain from the state of Santa Catarina, and compare them to the parameters set by existing international standards. Nine samples were collected, in which the properties were determined: size of pellets; bulk density and unity density; moisture content; immediate analysis; calorific value; mechanical durability and fines content. Compared to literature and quality standards parameters: the pellets showed high apparent density (663.46 kg / m3), unit density (1711 kg / m3), mechanical durability (99.07[%]) and gross calorific value (20.21 MJ / kg); low moisture content (7.89[%]) and ash (0.38[%]), indicating good quality pellets. The pellets had a high fines content (1.05[%]), as a negative characteristic. They had diameter of 6.58 mm; length 17.31 mm; volatiles content of 81.29[%] and 18.33[%] fixed carbon. The average values of properties of the pellets fully met the German standards (DIN Plus) and Austria (ÖNORM M7135) and G2 and G3 classes of Swedish (SS 187 120), and the classes I1, I2 and I3 ISO (17225-2), and can be used in the service and industry sectors.